Effect of high compared with low dairy intake on blood pressure in overweight middle-aged adults: results of a randomized crossover intervention study. Issue 2 (25th June 2019) - Rietsema, Susan; Eelderink, Coby; Joustra, Monica L; van Vliet, Iris M Y; van Londen, Marco; Corpeleijn, Eva; Singh-Povel, Cecile M; Geurts, Jan M W; Kootstra-Ros, Jenny E; Westerhuis, Ralf; Navis, Gerjan; Bakker, Stephan J L
ABSTRACT: Background: Observational studies suggest that high dairy intake is associated with a lower blood pressure (BP). Objective: We aimed to investigate the effect of a high-dairy diet (HDD) as compared with a low-dairy diet (LDD) on BP in overweight middle-aged adults. Methods: Fifty-two overweight men and women were included in a randomized crossover intervention study. Each subject consumed 2 isocaloric diets for 6 wk, an LDD (≤1 dairy portion per day) and an HDD (6 or 5 reduced-fat dairy portions for men and women, respectively), with a 4-wk washout period in between the diets during which the subjects consumed their habitual diet. BP was measured at the start and at the end of the intervention diets. The effect of the intervention study was evaluated by 2-sample t tests. Mixed-model analyses were used for adjustment for the potential influence of changes in dietary protein and mineral intake and risk factors for hypertension including body weight and plasma cholesterol. Results: Consumption of an HDD as compared with an LDD resulted in a reduction of both systolic BP (mean ± SD: 4.6 ± 11.2 mm Hg, P  < 0.01) and diastolic BP (3.0 ± 6.7 mm Hg, P  < 0.01). In further analyses, these reductions appeared dependent on the concomitant increase in calcium intake. Conclusions: This intervention study shows that an HDD results in a reduction of both systolic and diastolic BP in overweight middle-aged men and women. If the results of our study are reproduced by other studies, advice for high dairy intake may be added to treatment and prevention of high BP. This trial was registered at trialregister.nl as NTR4899.